Health : sculptured by the hands of culture : exploring the Ecuadorian worldview of health : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy of Development Studies at Massey University, New Zealand - Hicks, Ruth Miriam (Massey University, 2002)
Worldview is at the core of our being, providing the filter that gives form to our beliefs, values and behaviour. Each culture and country has its unique perspective in such vital areas such as health and wellbeing. In the global context, where 'health for all' is more a dream than reality, the challenge is to grasp the conceptual understanding of health in each context, to dialogue with the culture, and look for creative ways of meeting health needs. This thesis is part of my journey to achieve an understanding of this, in the context of Ecuador. The essence of this study is an exploration of the Ecuadorian context. How is health conceptualised within the culture? Is there a worldview of health? Are there areas of commonality of beliefs and practices in health? What are some of the historical events and processes that have formed this way of understanding? What has the ways of seeing health in Ecuador's current context? This thesis presents the experiences and knowledge collected during five months of focussed research and two years of lived experiences in Ecuador. It is very much a journey of discovery for the researcher and participants. The research methodology gives voice to the stories of four participatory groups and five in-depth interviews, which allowed the participants to share their knowledge and experience of health. Through the process of reviewing literature on the beliefs and practices throughout various non-western systems of healing, a number of elements were found common to all. These include: the interrelated nature of the physical and spiritual realms; the concept of self and community; origins of unwellness and health seeking practices; food and food practices; syncretism and the concept of body image. The stories of the participants reveal some of their beliefs and practices of health. Despite the wealth of cultural origins, climatic and contextual variety presented in Ecuador, nine themes emerge from the participants' stories, as common to their beliefs and practices of health: nature's healers, traditional sicknesses, the path of tradition, common sicknesses and causes of death, the therapeutic route, you are well if you look happy, of divine descent but humanly frail, no health without money, the path of tradition, and an acute awareness of the state of health. Together these portray a fascinating insight into part of the Ecuadorian worldview of health.
Keywords: Ecuador; Social life customs; Social medicine; Medical anthropology; Traditional medicine